2017
DOI: 10.1111/pbi.12696
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of BnDA1, whose gene locus is associated with the seeds weight, improves the seeds weight and organ size in Brassica napus

Abstract: Summary Brassica napus L. is an important oil crop worldwide and is the main raw material for biofuel. Seed weight and seed size are the main contributors to seed yield. DA1 (DA means big in Chinese) is an ubiquitin receptor and negatively regulates seed size. Down‐regulation of AtDA1 in Arabidopsis leads to larger seeds and organs by increasing cell proliferation in integuments. In this study, BnDA1 was down‐regulated in B. napus by over expressed of AtDA1 R358K, which is a functional deficiency of DA1 with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 45 publications
0
59
0
Order By: Relevance
“…Previous studies of DA1 focused on the AtDA1 R358K mutation in the da1‐1 dominant‐negative mutant. This mutation inhibited the activities of DA1 and DAR1, significantly increasing seed sizes in Arabidopsis , as well as transgenic rapeseed and maize (Li et al , ; Wang et al , ; Xie et al , ); however, this mutation has not been identified in natural variations so far. In this study, we sequenced many natural variations in TaDA1‐A , most of which were located in the promoter and intronic regions (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of DA1 focused on the AtDA1 R358K mutation in the da1‐1 dominant‐negative mutant. This mutation inhibited the activities of DA1 and DAR1, significantly increasing seed sizes in Arabidopsis , as well as transgenic rapeseed and maize (Li et al , ; Wang et al , ; Xie et al , ); however, this mutation has not been identified in natural variations so far. In this study, we sequenced many natural variations in TaDA1‐A , most of which were located in the promoter and intronic regions (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ubiquitin-proteasome pathways are involved in control of seed size (Li and Li, 2016 ; Nadolska-Orczyk et al , 2017 ; Kelley, 2018 ; Li et al , 2019 b ; Xu and Xue, 2019 ), and one of these, the DA1 pathway, plays a key role in controlling seed size in Arabidopsis by regulating cell proliferation in the integuments ( Disch et al , 2006 ; Xia et al , 2013 a ; Du et al , 2014 ; Li and Li, 2016 ; Dong et al , 2017 ). This pathway of control of seed size is highly conserved among species ( Su et al , 2011 ; Wang et al , 2017 ; Xie et al , 2018 ). For example, Grain Width and Weight2 ( GW2 ), a major quantitative trait locus (QTL) in rice, is a homolog of DA2 , a RING-type E3 ubiquitin ligase gene ( Song et al , 2007 ; Xia et al , 2013 a ).…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups worldwide have obtained transgenic or mutant plants exhibiting higher yields than controls (Zhao et al, 2015;Cabello et al, 2017;Wang et al, 2017;Jiang et al, 2018;Lim et al, 2018). However, the evaluation of stems width and the number of vascular bundles in these plants was not investigated or associated with seed yield.…”
Section: Introductionmentioning
confidence: 99%